Preparation of PLLA/PBAT-Strengthened Degradable Expanded Polystyrene - Do, Taegu; Ko, Young Gun; Chun, Youngsang; Shin, Young Kil; Kim, Young Gug; Choi, Ung Su (WILEY, 2017)
To enhance the flexural strength of degradable expanded polystyrene (DEPS) while maintaining degradability, during the manufacturing processes of DEPS, cerium(III) stearate (CeSt(3)) and poly-L-lactide (PLLA)/poly(butylene adipateco-terephthalate) (PBAT) are used as a nontoxic oxidizer and a co-biodegradable polymer filler, respectively. The flexural strength of DEPS is decreased by the oxidizer and increased by the biodegradable polymers. Furthermore, by favorable interfacial interaction between PLLA and PBAT, the flexural strength is more enhanced when the two biodegradable polymers are used simultaneously than used separately. The photo-, bio-and oxo-degradation behaviors of DEPS were evaluated by UV irradiation, thermal treatments, landfill, and non-landfill tests. Molecular weight of our DEPS is decreased to 90.26% after 2 weeks of UV irradiation and 74.4% after 3 months of thermal treatment test. 35.4 and 31.4% of weight of our DEPS is reduced after 3 months of landfill and non-landfill test. It is confirmed that the decomposition period of DEPS could be adjusted by controlling the amount of the oxidizer and/or the biodegradable polymers. The FT-IR study demonstrated that oligomers and nonylphenol which are known to cause the environmental hazards are not generated after the degradation of DEPS. POLYM. (C) 2016 Society of Plastics Engineers